A review of some south american species of jumping spiders (Araneae: Salticidae) described by Mello-Leitão from Brasil, with resolution of the genus Asaphobelis - Edwards, G. B.; Rinaldi, Isabela M. P. [UNESP]; Ruiz, Gustavo R. S. [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2005)
Os tipos de 18 espécies de Salticidae descritas por Mello-Leitão para o Brasil foram re-examinados e redescritos quando necessário. As seguintes mudanças nomenclaturais foram propostas: Novas sinonímias: Akela quinquevittata Mello-Leitão 1947 = Ilargus coccineus Simon 1901; Asaphobelis pluripunctatus Mello-Leitão 1947 = Asaphobelis physonychus Simon 1902; Asaracus elegantulus Mello-Leitão 1947 = Chira thysbe Simon 1902; Breda nigrotaeniata Mello-Leitão 1947 = Breda flavostriata Simon 1901; Phiale duplocellata Mello-Leitão 1947 = Phiale tristis Mello-Leitão 1945. Novas Combinações: Akela longibarba Mello-Leitão 1943 = Phiale longibarba (Mello-Leitão 1943); Marpissa broadwayi Peckham & Peckham 1892 (= Naubolus aureocomosus Mello-Leitão 1943) = Platycryptus broadwayi (Peckham & Peckham 1892); Saitis labyrintheus Mello-Leitão 1947 = Mopiopia labyrinthea (Mello-Leitão 1947) [lectótipo e paralectótipo designados]; Saitis tristis Mello-Leitão 1947 = Mopiopia tristis (Mello-Leitão 1947); Semora albibarbis Mello-Leitão 1947 = Tariona albibarbis (Mello-Leitão 1947); Asaphobelis fasciiventris Simon 1902 = Coryphasia fasciiventris (Simon 1902). Asaphobelis physonychus Simon 1902 agora e a única espécie no gênero. Outras espécies redescritas: Coryphasia castaneipedis Mello-Leitão 1947; Coryphasia nigriventris Mello-Leitão 1947; Cotinusa leucoprocta (Mello-Leitão 1947); Naubolus trifasciatus Mello-Leitão 1927; Phiale bipunctata Mello-Leitão 1947; Pseudofluda pulcherrima Mello-Leitão 1928; Semora langei Mello-Leitão 1947; e Titanattus pallidus Mello-Leitão 1943.

The types of 18 species of Salticidae described by Mello-Leitão from Brasil were re-examined and redescribed if necessary. The following nomenclatorial changes are made: New Synonyms: Akela quinquevittata Mello-Leitão 1947 = Ilargus coccineus Simon 1901; Asaphobelis pluripunctatus Mello-Leitão 1947 = Asaphobelis physonychus Simon 1902; Asaracus elegantulus Mello-Leitão 1947 = Chira thysbe Simon 1902; Breda nigrotaeniata Mello-Leitão 1947 = Breda flavostriata Simon 1901; Phiale duplocellata Mello-Leitão 1947 = Phiale tristis Mello-Leitão 1945. New Combinations: Akela longibarba Mello-Leitão 1943 = Phiale longibarba (Mello-Leitão 1943); Marpissa broadwayi Peckham & Peckham 1892 (= Naubolus aureocomosus Mello-Leitão 1943) = Platycryptus broadwayi (Peckham & Peckham 1892); Saitis labyrintheus Mello-Leitão 1947 = Mopiopia labyrinthea (Mello-Leitão 1947) [lectotype and paralectotype designated]; Saitis tristis Mello-Leitão 1947 = Mopiopia tristis (Mello-Leitão 1947); Semora albibarbis Mello-Leitão 1947 = Tariona albibarbis (Mello-Leitão 1947); Asaphobelis fasciiventris Simon 1902 = Coryphasia fasciiventris (Simon 1902). Asaphobelis physonychus Simon 1902 now is the only species in the genus. Other species redescribed are: Coryphasia castaneipedis Mello-Leitão 1947; Coryphasia nigriventris Mello-Leitão 1947; Cotinusa leucoprocta (Mello-Leitão 1947); Naubolus trifasciatus Mello-Leitão 1927; Phiale bipunctata Mello-Leitão 1947; Pseudofluda pulcherrima Mello-Leitão 1928; Semora langei Mello-Leitão 1947; and Titanattus pallidus Mello-Leitão 1943.
Keywords: Mello-Leitão; Brasil; Araneae; Salticidae; novas sinonímias; novas combinações; redescrições; Mello-Leitão; Brasil; Araneae; Salticidae; New Synonyms; New Combinations; Redescriptions